Optimalisasi Pemanfaatan Website Profil Desa Dalam Meningkatkan Perekonomian Warga Desa Paddinging Kecamatan Sanrobone Kabupaten Takalar - Ackhriansyah Ahmad Gani; Mahathir Mohammad (LPPM Universitas 17 Agustus 1945 Semarang, 2023)
There are many benefits to a village having a website that is managed seriously. Lighten the government's workload and make things easier for village communities. This service activity will be carried out in Paddinging Village, which is one of the villages in Sanrobone District, Takalar Regency, South Sulawesi. This consideration regarding location selection is because Paddinging Village does not yet have a village website. On the other hand, Paddinging Village has several natural potentials which can be maximized by disseminating information to people inside and outside the village. Paddinging Village has quite large natural and tourism potential but has not received special attention from the government. The expanse of mountains and rice fields as well as the mist that sometimes covers it, accompanied by cool air are the characteristics of Paddinging Village. Apart from that, Paddinging Village has a pine forest which is very suitable as a camping spot on the weekend. Even the water there comes from springs directly from the mountains, which can be used as a basic ingredient for a mineral drinking water business.